The conservative treatment of longstanding adductor-related groin pain syndrome: a critical and systematic review - Bisciotti, Gian Nicola; Chamari, Karim; Cena, Emanuele; Garcia, Gonzalo Rodriguez; Vuckovic, Zarko; Bisciotti, Alessandro; Bisciotti, Andrea; Zini, Raul; Corsini, Alessandro; Volpi, Piero (Biology of Sport, 2021)
Longstanding (chronic) adductor-related groin pain syndrome is a widely common problem for athletes in many sports activities which often drastically reduces player activity and performance. The first choice in therapeutic treatment is conservative therapy. The objective of this study is to provide a systematic review regarding conservative treatment for longstanding adductor-related groin pain syndrome present in literature today. Furthermore, this study aims to give a critical vision of the current state of the art of the considered topic. After screening 234 articles, 19 studies following the inclusion criteria were included and summarized in this current systematic review and seven different types of therapeutic interventions were described. Compression clothing therapy, manual therapy together with strengthening exercise and prolotherapy were the therapeutic interventions which showed both the greatest level of strength of evidence (Moderate) and grade of recommendation (D). The remaining four types of therapeutic interventions i.e.: corticoid injection, platelet rich plasma therapy, intra-tissue percutaneous electrolysis and pulse-dose radiofrequency, showed both lower levels of strength of evidence (Conflicting) and grade of recommendation (C). In conclusion the literature available on the conservative treatment for longstanding adductor-related groin pain syndrome is limited and characterized by a low level of evidence. Therefore, our recommendation is to refer only to the few studies with higher level of evidence and at the same time to encourage further research in this area. The intervention showing the greater level of strength of evidence, and the greater grade of recommendation are compression clothing therapy, manual therapy and strengthening exercise, and prolotherapy. Other therapeutic interventions such as intra-tissue percutaneous electrolysis and pulse-dose radiofrequency seem promising but require further studies to confirm their efficacy.